EMPLOYEES’ OPTIMISM AND ORGANIZATIONAL COMMITMENT: A STUDY OF SELECTED BANKS IN THE NIGER DELTA REGION OF NIGERIA - Nwibere, B. M; Worlu, G.O. (Scholars Digest Publishing, 2023)
This study empirically investigated the relationship between employees’ psychological optimism and organisational commitment. The sample comprised 280 managerial and non-managerial employees from seven randomly selected banks in the Niger Delta Region of Nigeria. The study adopted a quasi-experimental research design as it is deemed appropriate for the administrative sciences, incorporating both primary and secondary data. Data analysis was conducted using the Spearman Rank Correlation Coefficient, employing the Statistical Package for Social Sciences (SPSS) version 20. The findings revealed a positive and significant relationship between employees’ psychological optimism and organisational commitment. Specifically, employees’ psychological optimism was found to positively and significantly impact various dimensions of organisational commitment, including affective, normative, and continuance commitment. In light of these results, it is imperative for managers of Nigerian banks to effectively cultivate employees’ optimism to enhance their commitment to the organization. Additionally, the study outlines other practical implications for managing employees’ psychological optimism and organisational commitment within the Nigerian workplace.